Basal Ganglia and Cortex Repair through Human Repair-Neurophysiology 12 Years after Hypoxia during Birth - Giselher Schalow (Human Repair-Neurophysiology, 2022)
The patient Alen suffered at birth an insult and an asphyxia with the consequence of a sustained cerebral hemiplegia on the left side, a parenchyma defect of the basal ganglia and a degeneration of a pyramidal tract. At an age of 12 years coordination dynamics therapy was started. Most functions were impaired in Alen. He could not use the left hand, which is a disability of 50%. But he could walk and run with deficits. Through 6 months of coordination dynamics therapy, creeping, crawling, walking and running became nearly normal. He learned to jump in-phase and in anti-phase. Most importantly, he learned left hand functions, including the power and precision grip, and could use them for everyday life. His cognitive functions improved. He could better learn at school. What main stream medicine did not achieve in 12 years; coordination dynamics therapy succeeded in 6 months.